Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.